Molecular evidence of Chlamydia pecorum and arthropod-associated Chlamydiae in an expanded range of marsupials. Issue 1 (December 2017) - Burnard, Delaney; Huston, Wilhelmina; Webb, Jonathan; Jelocnik, Martina; Reiss, Andrea; Gillett, Amber; Fitzgibbon, Sean; Carver, Scott; Carrucan, Janine; Flanagan, Cheyne; Timms, Peter; Polkinghorne, Adam
Abstract The orderChlamydiales are biphasic intracellular bacterial pathogens infecting humans and domesticated animals. Wildlife infections have also been reported, with the most studied example beingChlamydia pecorum infections in the koala, an iconic Australian marsupial. In koalas, molecular evidence suggests that spill-over fromC. pecorum infected livestock imported into Australia may have had a historical or contemporary role. Despite preliminary evidence that other native Australian marsupials also carryC. pecorum, their potential as reservoirs of this pathogen and otherChlamydia -related bacteria (CRBs) has been understudied. Mucosal epithelial samples collected from over 200 native Australian marsupials of different species and geographic regions across Australia were PCR screened forChlamydiales . Previously described and genetically distinctC. pecorum genotypes and a range of 16S rRNA genotypes sharing similarity to different CRBs in the broaderChlamydiales order were present. One 16S rRNAChlamydiales genotype recently described in Australian ticks that parasitise native Australian marsupials was also identified. This study provides further evidence that chlamydial infections are widespread in native fauna and that detailed investigations are required to understand the influence these infections have on host species conservation, but also whether infection spill-over plays a role in their epidemiology.